WORKING PERFORMANCE OF STUDENT SPORT CENTER MANAGEMENT IN NORTH SUMATERA (A Correlation Study between Job Satisfaction and Management Knowledge and Working Performance of Student Sport Center Management in North Sumatera) - Ratno, Puji; Fadli, Zen (Universitas Negeri Medan, 2017)
Abstract This current study was conducted to arrive at the scientific and accurate answer to decide whether there was correlation between Job Satisfaction and Management Knowledge and Working Performance of Student Sport Center Management, either working individually or collaboratively. Management team of Training and Development in Student Sport Center North Sumatera as many as 30 people were chosen as the subjects of this current study. This study was conducted on February-March 2012. This research used correlation approach technique in taking samples by using total sampling. It was concluded that: 1) There was a significant correlation between Job Satisfaction and Working Performance of Training and Development Management of Student Sport Center North Sumatera, which resulted t-count = 5.20 > t-table = 1.70; 2) There was a significant correlation between Management Knowledge and Working Performance of Training and Development Management of Student Sport Center North Sumatera, which resulted t-count = 3.32> t-table = 1.70; and 3) There was a significant correlation between Job Satisfaction and Management Knowledge and Performance of Training and Development Management of Student Sport Center North Sumatera, which resulted F-count =20.37 > F-table = 3.35. Key words: job satisfaction, management knowledge, performance